2016
DOI: 10.1016/j.jaac.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Trajectories of Suicidal Thoughts and Behaviors From Adolescence Through Adulthood

Abstract: Objective Little is known about the patterns among individuals in the long-term course of suicidal thoughts and behaviors (STBs). The objective of this study was to identify developmental trajectories of STBs from adolescence through young adulthood, as well as risk and protective covariates, and nonsuicidal outcomes associated with these trajectories. Method 180 adolescents (ages 12–18 at recruitment) were repeatedly assessed over an average of 13.6 years (2,273 assessments) since their psychiatric hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 52 publications
4
51
1
1
Order By: Relevance
“…The potential mechanisms underlying this relationship require further study but could include genetic influences, imitation, social transmission and assortative relating. In contrast to these findings, a recent study of hospitalised adolescents found no association between family history of suicidal behaviour and suicidal ideation/behaviours (Goldston et al., ). Our sample was population‐based, and we were not able to explore associations with hospitalisation/service use.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The potential mechanisms underlying this relationship require further study but could include genetic influences, imitation, social transmission and assortative relating. In contrast to these findings, a recent study of hospitalised adolescents found no association between family history of suicidal behaviour and suicidal ideation/behaviours (Goldston et al., ). Our sample was population‐based, and we were not able to explore associations with hospitalisation/service use.…”
Section: Discussionmentioning
confidence: 80%
“…There is increasing evidence from both clinical and population‐based samples that one of these risk factors, exposure to self‐harm in others, reliably distinguishes between young people with suicidal ideation and attempts (Asarnow et al., ; Dhingra, Boduszek, & O'Connor, ; O'Connor & Nock, ). Other factors that have been found to be associated with suicide attempts amongst ideators in this age group include mental health problems, aggression, impulsivity, substance abuse, female gender, stressful life events, abuse, relationship problems, pregnancy events and factors relating to service use/treatment (Asarnow et al., ; Borges, Benjet, Medina‐Mora, Orozco, & Nock, ; Goldston et al., ; Nock et al., ; O'Connor, Rasmussen, & Hawton, ; Taliaferro & Muehlenkamp, ). However, effect sizes are often small, and findings have frequently been inconsistent across studies or have not been replicated.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies find different phenotypes based on risk factors for suicidal thoughts and several others have examined profiles of suicidal thinking based on the trajectory of suicidal thinking measured weeks or months apart (Czyz & King, 2015;Goldston et al, 2016;Wolff et al, 2018), no prior studies have examined whether there are different phenotypes of suicidal thoughts based on the actual experience of thoughts itself. Recent theoretical work by Bernanke, Stanley, and Oquendo (2017) suggests that there may be at least two subtypes of the experience of suicidal thinking.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, suicide is the second leading cause of death in young populations [8]. Suicidal behavior among children and adolescents is, however, different to that reported in adult populations [9]. Prevalence rates seem to vary not only by age but also by gender.…”
Section: Introductionmentioning
confidence: 95%